Level, pattern and socio-economic determinants of enrollment informal schools of the graduates of BRAC's education programme - Nath, Samir Ranjan (BRAC Research and Evaluation Division (RED), 2019)
BRAC has been operating two models of primary education for the children of poor households in Bangladesh since 1985. After graduation from BRAC schools, these children enroll in formal schools for further education. This study identified the level, pattern and determinants of enrollment in formal schools who graduated from BRAC schools. Information of 1,259 children was collected at the end of 1995. Both bivariate and multivariate analyses were performed. This study reveals that about 80% of the graduates of BRAC's education programme were continuing their education in formal schools. No gender variation in enrollment was found. Findings also indicated that younger graduates whose mothers have some schooling and who were non-eligible for BRAC membership were more likely to get further education in formal schools compared to other groups. Availability of formal school in their own village was also found as a determinant of girls enrollment. Considering the underdeveloped socio-economic condition of Bangladesh, this study concludes that enrollment rate of the graduates was satisfactory. Measures such as motivation to the parents and supervision of the programme organisers (POs) of BRAC may be taken for further improvement of the current situation.